Original paperEffect of diameter of nanoparticles and capture cross-section library on macroscopic dose enhancement in boron neutron capture therapy - Farhood, Bagher; Ghorbani, Mahdi (Journal of Contemporary Brachytherapy, 2014)
Purpose : The aim of this study is evaluation of the effect of diameter of 10 B nanoparticles and various neutron capture cross-section libraries on macroscopic dose enhancement in boron neutron capture therapy (BNCT). Material and methods : MCNPX Monte Carlo code was used for simulation of a  252 Cf source, a soft tissue phantom and a tumor containing 10 B nanoparticles. Using 252 Cf as a neutron source, macroscopic dose enhancement factor (MDEF) and total dose rate in tumor in the presence of 100, 200, and 500 ppm of 10 B nanoparticles with 25 nm, 50 nm, and 100 nm diameters were calculated. Additionally, the effect of ENDF, JEFF, JENDL, and CENDL neutron capture cross-section libraries on MDEF was evaluated. Results : There is not a linear relationship between the average MDEF value and nanoparticles’ diameter but the average MDEF grows with increased concentration of 10 B nanoparticles. There is an increasing trend for average MDEF with the tumor distance. The average MDEF values were obtained the same for various neutron capture cross-section libraries. The maximum and minimum doses that effect on the total dose in tumor were neutron and secondary photon doses, respectively. Furthermore, the boron capture related dose component reduced in some extent with increase of diameter of 10 B nanoparticles. Conclusions : Based on the results of this study, it can be concluded that from physical point of view, various nanoparticle diameters have no dominant effect on average MDEF value in tumor. Furthermore, it is concluded that various neutron capture cross-section libraries are resulted to the same macroscopic dose enhancements. However, it is predicted that taking into account the biological effects for various nanoparticle diameters will result in different dose enhancements.